2021
DOI: 10.3389/fimmu.2021.727254
|View full text |Cite
|
Sign up to set email alerts
|

PD-1 Blockade Restores the Proliferation of Peripheral Blood Lymphocyte and Inhibits Lymphocyte Apoptosis in a BALB/c Mouse Model of CP BVDV Acute Infection

Abstract: Acute infection of bovine viral diarrhea virus (BVDV) is associated with immune dysfunction and can cause peripheral blood lymphopenia and lymphocyte apoptosis. Our previous study has confirmed that programmed death-1 (PD-1) blockade inhibits peripheral blood lymphocytes (PBL) apoptosis and restores proliferation and anti-viral immune functions of lymphocytes after BVDV infection in vitro. However, the situation in vivo remains to be further studied and confirmed. Therefore, in this study, we established a BAL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 49 publications
1
12
0
Order By: Relevance
“…The anti-CP BVDV effects of phlorizin were significant. In previous studies, we have successfully established the mouse model of BVDV infection and confirmed that the viral load in the tissues and blood of mice was high and the histopathological change was evident at 7 d post-infection . In the present study, the protective effects of phlorizin on CP BVDV-infected mice were explored, taking the mouse as a model.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…The anti-CP BVDV effects of phlorizin were significant. In previous studies, we have successfully established the mouse model of BVDV infection and confirmed that the viral load in the tissues and blood of mice was high and the histopathological change was evident at 7 d post-infection . In the present study, the protective effects of phlorizin on CP BVDV-infected mice were explored, taking the mouse as a model.…”
Section: Discussionsupporting
confidence: 51%
“…The mouse model of BVDV infection was established according to our previous reports . In the present study, BALB/c mice were randomly equally divided into six groups of six mice each to explore the effects of phlorizin on CP BVDV infection as follows: control group, BVDV group, phlorizin (6.25, 12.5, and 25 mg/kg) + BVDV groups, and phlorizin (25 mg/kg) group.…”
Section: Materials and Methodsmentioning
confidence: 99%
“…A previous study reported that classical swine fever virus (CSFV) could induce lymphocyte apoptosis during infection ( 40 ). Recently, researchers have confirmed that BVDV could promote the expression of PD-1 to induce peripheral blood lymphocyte apoptosis ( 41 ). In this study, we observed that certain anti-apoptotic proteins such as BCL2A1, BIRC3, and NGF were significantly down-regulated in the BVDV-infected MDBK cells compared to their levels in the mock-infected MDBK cells.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous studies, we established a mouse model of BVDV infection [1]. In this study, we divided the mice into cp BVDV infection group, ncp BVDV infection group, control group, 50 mg/kg quercetin administration group, 100 mg/kg quercetin administration group, DMSO control group, 50 mg/kg quercetin + cp BVDV group, 50 mg/kg quercetin + ncp BVDV group, 100 mg/kg quercetin + cp BVDV group, and 100 mg/kg quercetin + ncp BVDV group.…”
Section: Bvdv Animal Infection Modelmentioning
confidence: 99%
“…Bovine viral diarrhea virus (BVDV), a positive-strand RNA virus of the genus Pestivirus in the Flaviviridae family, is the causative agent of viral diarrheal disease in bovines. Flaviviridae also includes critical human pathogens, such as West Nile virus (WNV), hepatitis C virus (HCV), yellow fever virus (YFV), dengue virus (DV), and Saint Louis encephalitis virus (SLEV) [1]. Acute infection of BVDV is associated with immune dysfunction and can cause peripheral blood lymphopenia and apoptosis.…”
Section: Introductionmentioning
confidence: 99%